Application of the Novel Ventilation Mode FLow-Controlled EXpiration (FLEX): A Crossover Proof-of-Principle Study in Lung-Healthy Patients. (October 2017) - Wirth, Steffen; Springer, Sebastian; Spaeth, Johannes; Borgmann, Silke; Goebel, Ulrich; Schumann, Stefan
Abstract : BACKGROUND: Traditionally, mechanical ventilation is achieved via active lung inflation during inspiration and passive lung emptying during expiration. By contrast, the novel FLEX (FLow-controlled EXpiration) ventilator mode actively decreases the rate of lung emptying. We investigated whether FLEX can be used during intraoperative mechanical ventilation of lung-healthy patients. METHODS: In 30 adult patients scheduled for neurosurgical procedures, we studied respiratory system mechanics, regional ventilation, oxygenation, and hemodynamics during ventilation with and without FLEX at positive end-expiratory pressure (PEEP) of 5 and 7 cm H2 O. The FLEX system was integrated into the expiratory limb and modified the expiratory flow profile by continuously changing expiratory resistance according to a computer-controlled algorithm. RESULTS: Mean airway pressure increased with PEEP by 1.9 cm H2 O and with FLEX by 1 cm H2 O (all P < .001). The expiratory peak flow was 42% lower with FLEX than without FLEX ( P < .001). FLEX caused significant shifts in aeration from ventral to the dorsal lung regions. Respiratory mechanics, end-tidal carbon dioxide partial pressure, oxygenation, and hemodynamics were independent from FLEX and PEEP. We observed no critical incidents or FLEX malfunctions in any measurement that would have required an intervention or termination of the FLEX mode. CONCLUSIONS: FLEX can be used in lung-healthy patients who are mechanically ventilated during general anesthesia. FLEX improves the homogeneous distribution of ventilation in the lungs. Abstract : Supplemental Digital Content is available in the text.Published ahead of print April 3, 2017.